Dose and setting of rehabilitation received after stroke in Queensland, Australia: a prospective cohort study. (June 2020) - Grimley, Rohan S; Rosbergen, Ingrid CM; Gustafsson, Louise; Horton, Eleanor; Green, Theresa; Cadigan, Greg; Kuys, Suzanne; Andrew, Nadine E; Cadilhac, Dominique A
Objective: The aims of this study were to describe patterns and dose of rehabilitation received following stroke and to investigate their relationship with outcomes. Design: This was a prospective observational cohort study. Setting: A total of seven public hospitals and all subsequent rehabilitation services in Queensland, Australia, participated in the study. Subjects: Participants were consecutive patients surviving acute stroke between July 2016 and January 2017. Methods: We tracked rehabilitation for six months following stroke and obtained 90- to 180-day outcomes from the Australian Stroke Clinical Registry. Measures: Dose of rehabilitation – time in therapy by physiotherapy, occupational therapy and speech pathology; modified Rankin Scale (mRS)- premorbid, acute care discharge and 90- to 180-day follow-up. Results: We recruited 504 patients, of whom 337 (median age = 73 years, 41% female) received 643 episodes of rehabilitation in 83 different services. Initial rehabilitation was predominantly inpatient (260/337, 77%) versus community-based (77/337, 21%). Therapy time was greater within inpatient services (median = 29 hours) compared to community-based (6 hours) or transition care (16 hours). Median (Quartile 1, Quartile 3) six-month cumulative therapy time was 73 hours (40, 130) when rehabilitation commenced in stroke units and continued in inpatient rehabilitation units; 43 hours (23, 78) when commenced in inpatient rehabilitation units; and 5 hours (2, 9) with only community rehabilitation. In 317 of 504 (63%) with follow-up data, improvement in mRS was most likely with inpatient rehabilitation (OR = 3.6, 95% CI = 1.7–7.7), lower with community rehabilitation (OR = 1.6, 95% CI = 0.7–3.8) compared to no rehabilitation, after adjustment for baseline factors. Conclusion: Amount of therapy varied widely between rehabilitation pathways. Amount of therapy and chance of improvement in function were highest with inpatient rehabilitation.